2023
DOI: 10.24072/pcjournal.238
|View full text |Cite
|
Sign up to set email alerts
|

The fate of recessive deleterious or overdominant mutations near mating-type loci under partial selfing

Abstract: Large regions of suppressed recombination having extended over time occur in many organisms around genes involved in mating compatibility (sex-determining or mating-type genes). The sheltering of deleterious alleles has been proposed to be involved in such expansions. However, the dynamics of deleterious mutations partially linked to genes involved in mating compatibility are not well understood, especially in finite populations. In particular, under what conditions deleterious mutations are likely to be maint… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Investigating whether DC always evolves, at least for dosage-sensitive genes, for old degenerate sex chromosomes would also be interesting, to confirm the key role of DC in their long-term stability. Several cases of interest should be investigated further, notably cases involving non-random mating (Charlesworth & Wall, 1999;Olito et al, 2022;Tezenas et al, 2023) or UV and mating-type chromosomes. Analytical models are needed to generalize the recent findings that have mostly been explored by simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating whether DC always evolves, at least for dosage-sensitive genes, for old degenerate sex chromosomes would also be interesting, to confirm the key role of DC in their long-term stability. Several cases of interest should be investigated further, notably cases involving non-random mating (Charlesworth & Wall, 1999;Olito et al, 2022;Tezenas et al, 2023) or UV and mating-type chromosomes. Analytical models are needed to generalize the recent findings that have mostly been explored by simulation.…”
Section: Discussionmentioning
confidence: 99%
“…While the widespread occurrence of DC [72,73] indicates that it is needed at least for some genes, it would be interesting to introduce heterogeneity among genes in selection on dosage, and varying the genetic architecture of DC (local vs global). Several cases of interest should be investigated further, notably cases involving non-random mating [18,29,74] or UV and mating-type chromosomes. Analytical models are needed to generalize the recent findings that have mostly been explored by simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating whether DC always evolves, at least for dosage-sensitive genes, for old degenerate sex chromosomes would also be interesting, to confirm the key role of DC in their long-term stability. Several cases of interest should be investigated further, notably cases involving non-random mating [18,29,82] or UV and mating-type chromosomes. Analytical models are needed to generalize the recent findings that have mostly been explored by simulation.…”
Section: Discussionmentioning
confidence: 99%
“…The deterministic model by Leach et al (1986) showed that very tight linkage is required for effective sheltering of lethal recessive mutations. More recently, Tezenas et al (2023) predicted using analytical and numerical modeling that even though the deleterious mutations partially linked to a fungal-like mating-type locus (where two alleles segregate as nonrecombining haplotypes) are almost surely purged, a limited fraction of them may persist for extended periods of time. Charlesworth et al (1997) showed that sites linked to a locus under balancing selection evolve in a manner that is analogous to a geographically subdivided population, where each of the balanced allelic line has a small effective population size, and mildly deleterious linked mutations can rise to intermediate or high frequencies within them by genetic drift.…”
Section: Introductionmentioning
confidence: 99%